2014
DOI: 10.5296/jbls.v6i1.6463
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pesticides on Haematology, Thyroid Stimulating Hormone (TSH) and Tri-iodothyronine (T3) Hormones of Agricultural Workers in Swat, Pakistan

Abstract: Swat valley is famous for its high production of agriculture crops. These crops are under constant attacks by different pests and use of pesticides has become very crucial for the control of these pests. Pesticides are toxic substances used to kill organisms which are competing humans for food and may also pose risk to humans. The current study was performed to investigate the effects of pesticides on blood circulating hormones (Thyroid stimulating hormone [TSH], Tri-iodothyronine [T3], and haematological para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…WBC, HB, HCT, MCV, MCHC, PLT, MPV, and PCT were also appreciably (P < 0.05; Multivariate regression ANOVA) altered with pesticide concentrations detected in their blood. (Quraishi et al 2015) showed an increase in WBC, Hb, PCV and MCV levels of farmers exposed to pesticides compared to the control group, but the platelet count in samples exposed to pesticides decreased compared to the controls. This change may be due to exposure to several different pesticides.…”
Section: Determination Of Hemotoxic Effectsmentioning
confidence: 77%
“…WBC, HB, HCT, MCV, MCHC, PLT, MPV, and PCT were also appreciably (P < 0.05; Multivariate regression ANOVA) altered with pesticide concentrations detected in their blood. (Quraishi et al 2015) showed an increase in WBC, Hb, PCV and MCV levels of farmers exposed to pesticides compared to the control group, but the platelet count in samples exposed to pesticides decreased compared to the controls. This change may be due to exposure to several different pesticides.…”
Section: Determination Of Hemotoxic Effectsmentioning
confidence: 77%
“…Different results were obtained through studies evaluating T 3 and exposure to various types of pesticides. Two articles showed that T 3 serum levels among exposed groups were significantly higher compared to the unexposed (44,46), but three demonstrated the opposite results (40,42,51).…”
Section: Discussionmentioning
confidence: 97%
“…According to Table 1, 11 articles evaluated pesticide exposure among male farmers or farmworkers (37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47) and six studies were conducted with either pesticide applicators or sprayers (36,(48)(49)(50)(51). Fifteen studies measured serum levels of thyroid hormones including Thyroid Stimulating Hormone (TSH), Free Triiodothyronine (FT 3 ), Free Thyroxine (FT 4 ), Triiodothyronine (T 3 ), Thyroxine (T 4 ), and Total Triiodothyronine (T 3 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both T3 and T4 are bio-indicators of the hypothalamus and pituitary glands activities (Kirsten, 2000;Mebis et al, 2008). These hormones have important function in the body, specifically the stimulation of metabolism (Puri, 2011;Quraishi et al, 2015). T3 and T4 help acquiring the element iodine and convert it into the form that is biologically available (Granner, 2003).…”
Section: Effects Of Abamectin and Indoxacarb On Hormones Adverse Effementioning
confidence: 99%